2006
DOI: 10.1002/humu.20332
|View full text |Cite
|
Sign up to set email alerts
|

Megalencephalic leukoencephalopathy with subcortical cysts: an update and extended mutation analysis ofMLC1

Abstract: Megalencephalic leukoencephalopathy with subcortical cysts (MLC) is an autosomal recessive cerebral white matter disorder in children. This disease is histopathologically characterized by myelin splitting and intramyelinic vacuole formation. MLC is caused by mutations in the gene MLC1, which encodes a novel protein, MLC1. Since the first report, 50 mutations in this gene have been found. Mutations occur throughout the entire coding region and include all different types: 11 splice-site mutations; one nonsense … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(29 citation statements)
references
References 28 publications
1
26
1
Order By: Relevance
“…Another research showed that mutation C326R reduced MLC1 mRNA expression [20]. Further, decline of MLC1 protein and mRNA expression had also been found in monocytes from MLC patients [31].…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Another research showed that mutation C326R reduced MLC1 mRNA expression [20]. Further, decline of MLC1 protein and mRNA expression had also been found in monocytes from MLC patients [31].…”
Section: Discussionmentioning
confidence: 91%
“…Until now, there are around 70 MLC-related mutations of MLC1 have been reported in patients of various ethnic backgrounds (human gene mutation database, HGMD). Despite this, families without identifiable mutation at the MLC1 locus had been found [3], [20], and the existence of at least one other locus had been suggested before [21], [22]. Recently, López-Hernández T et al found mutations in GlialCAM encoded by HEPACAM in some MLC patients without MLC1 mutations.…”
Section: Introductionmentioning
confidence: 99%
“…Of the core nine genes shared in all three progenitor niches, some are known NSC regulatory genes ( Sox2 , Ascl1 , Lxn , Id4 ), whereas others ( Mlc1 , Gja1 , Cd63 ) are human disease genes that now represent candidate regulatory pathways that serve a common role in regulating different CNS progenitors. Of these, Mlc1 deserves particular attention for its potential function in postnatal progenitors, as mutations in Mlc1 lead to the chronic demyelinating disorder Megalencephalic leukoencephalopathy with Subcortical Cysts- a disease that features an over-production of neural cells early during the first year of life that results in a paucity of myelin and macrocephaly [27]. Although Mlc1 function is uncharacterized, its enrichment in all three NSC niches suggests a regulatory role in postnatal progenitor proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Megalencephalic leukoencephalopathy with subcortical cysts (MLC) is a heritable human disease associated with loss-of-function mutations in the MLC1 gene (Ilja Boor et al ., 2006; Leegwater et al ., 2001; van der Knaap et al ., 1995). Mlc1 is a 38-kDa domain protein and shares sequence homology with K + ion channels (Boor et al ., 2005).…”
Section: Introductionmentioning
confidence: 99%